Delivery of Education Services in Lao PDR : Results of the SABER Service Delivery Survey, 2017 - Demas, Angela (World Bank, Washington, DC, 2021)
The SABER Service Delivery (SABER SD) survey instrument was developed as an initiative to uncover bottlenecks that inhibit student learning in low and middle-income countries and to better understand the quality of education service delivery in a country as well as gaps in policy implementation. SABER SD was created using knowledge and expertise from two major initiatives at the World Bank: SABER (Systems Approach for Better Education Results) and the SDI (Service Delivery Indicators) tools. The instrument collects data at the school level and asks questions related to the roles of all levels of government (including local and regional). The new instrument collects data at the school level and enables analysis on: (i) teacher effort and ability, (ii) principal leadership, (iii) school governance, management, and finances, (iv) community participation, (v) classroom observation, and (vi) student performance in math and language.